It's all in your brain - Funston, Sylvia; Ingram, Jay Clement, Gary (Grosset & Dunlap New York, 1994)
An interactive volume discusses the brain's role in thoughts, dreams, senses, emotions, and memories, utilizing an accessible, magazine-style format that combines factual text with cartoon-like artwork